Food and nutrition security in Addis Ababa, Ethiopia during COVID-19 pandemic: May 2020 report - Hirvonen, Kalle; Abate, Gashaw T.; de Brauw, Alan (International Food Policy Research Institute, 2020)
We called by telephone a representative sample of 600 households in Addis Ababa, Ethiopia to assess household food and nutrition security status during the COVID-19 pandemic. More than half the households indicated that their incomes were lower than expected and more than one-third reported that they are extremely stressed about the situation. Using a pre-pandemic wealth index, we find that less-wealthy households were considerably more likely to report income losses and high stress levels than were wealthier households. Compared to a period just before the pandemic (January and February 2020), indicators measuring food security have significantly worsened. In April, households were less frequently consuming relatively more expensive but nutritionally richer foods, such as fruit and dairy products. However, overall food security status in Addis Ababa is not yet alarming, possibly because most households have used their savings to buffer food consumption. It is likely that these savings will not last for much longer, calling for a rapid scale-up of existing support programs.